Locating histories of crime. A bibliographical study - King, Peter (The British journal of criminology, 1999)
This article aims to assist both criminologists wishing to access historical work in their particular subfields and historians coming to the history of crime for the first time by providing a guide to the ways in which material on the history of crime and criminal justice can be most easily accessed. It reviews introductory texts, existing printed bibliographies and important works whose bibliographies offer good starting points. It then looks at specialist journals and IT-based sources before pinpointing briefly a few works that may provide inspiration as well as information. It focuses primarily on England but also suggests ways into the wider literature